1997
DOI: 10.1098/rstb.1997.0157
|View full text |Cite
|
Sign up to set email alerts
|

Transient global amnesia and functional retrograde amnesia: contrasting examples of episodic memory loss

Abstract: We studied 11 patients with transient global amnesia (TGA) and ten patients with functional retrograde amnesia (FRA). Patients with TGA had a uniform clinical picture: a severe, relatively isolated amnesic syndrome that started suddenly, persisted for 4^12 h, and then gradually improved to essentially normal over the next 12^24 h. During the episode, the patients had severe anterograde amnesia for verbal and non-verbal material and retrograde amnesia that typically covered at least two decades. Thirty hours to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…Some studies with TGA patients yielded no graded autobiographical memory loss in the sense of Ribot, possibly because of the variability of methods and testing, the temporal dynamics of the recovery from TGA, and hence the time point of testing (32). Notably, similar to our results, earlier studies in TGA also observed a temporal gradient with regard to semantic memory compatible with the possibility that hippocampal lesions also gradually affect semantic memory (30)(31)(32)(33)(34). Using PET, patients with Alzheimer's disease show a temporally graded autobiographical amnesia reflected in a gradual disengagement of the hippocampus in the recall of autobiographical memories for remote memories (29).…”
Section: Discussionsupporting
confidence: 80%
“…Some studies with TGA patients yielded no graded autobiographical memory loss in the sense of Ribot, possibly because of the variability of methods and testing, the temporal dynamics of the recovery from TGA, and hence the time point of testing (32). Notably, similar to our results, earlier studies in TGA also observed a temporal gradient with regard to semantic memory compatible with the possibility that hippocampal lesions also gradually affect semantic memory (30)(31)(32)(33)(34). Using PET, patients with Alzheimer's disease show a temporally graded autobiographical amnesia reflected in a gradual disengagement of the hippocampus in the recall of autobiographical memories for remote memories (29).…”
Section: Discussionsupporting
confidence: 80%
“…R. Miller & Matzel, 2006;Riccio & Richardson, 1984;Spear, 1973 Brown, 2002;Squire & Alvarez, 1995). However, it is also common to observe that the 'forgotten' time period occurring prior to injury 'shrinks' with the passage of time (e.g., Russell & Nathan, 1946; also see Kritchevsky, Zouzounis, & Squire, 1997). This is similar to 'spontaneous recovery' e ects reported in extinction, counter-conditioning (Bouton, 2002), and pairedassociate learning studies (A.…”
Section: Recovery From Experimentally-induced Amnesiasupporting
confidence: 58%
“…One of the 10 patients confessed to malingering his amnesia, and his test scores are presented here so that they can be compared to the scores of the other patients. Preliminary findings for these patients appeared in an earlier report, which compared functional amnesia with transient global amnesia (Kritchevsky et al 1997).…”
mentioning
confidence: 98%